When Is High Turnover Cheaper? A Simple Model of Cost Tradeoffs in a Long-Distance Truckload Motor Carrier, with Empirical Evidence and Policy Implications - Stephen V. Burks; Arne Kildegaard; Jason W. Miller; Kristen Monaco (Institute of Labor Economics (IZA), 2023)
The U.S. trucking industry has been calling out a shortage of truck drivers for nearly forty years, since soon after its economic deregulation in 1980. Burks and Monaco (2019) provided evidence that the overall truck driver labor market works about as well as any blue collar labor market, and suggested persistently high driver turnover uniquely at long-distance truckload firms (central to long distance freight but employing only 20% of tractor-trailer truckers) drives the shortage perception. The American Trucking Associations (ATA) agreed with the location of the problem, but argued that a driver shortage and high turnover are distinct, and that a long-term shortage does exist. We review the evidence for a shortage and find it unconvincing. We also review empirical evidence that long-distance truckload has had persistently high-turnover since the mid-1980s. To explain this, we provide a simple model of long-distance truckload cost minimization in which there is a tradeoff between the costs of turnover and two other costs, higher pay to offset bad working conditions (compensating differentials), and running trucks out-of- route to get drivers home regularly (inefficient capital use). We show that high turnover is likely structural because it is part of the least-cost mixture. We then use our model to analyze the potential impacts of two technological changes (truck simulators and partially automated trucks), and a key policy championed by the ATA to "fix the shortage," interstate teenaged truckers. We show that these are likely to have results opposite to those the industry and policy makers expect.
Keywords: L1; J42; L9; 330; costs; less-than-truckload; truckload; driver shortage; driver turnover; long-distance motor carrier; teenaged truck drivers; partially automated trucks; truck transportation